Promoting the Sale of Locally Sourced Products: Km 0 as a Sustainable Model for Local Agriculture and CO2 Reduction - Alejandro Martínez-Vérez; Cristina Lucini Baquero (Agriculture)
The commercialization of Km 0 agricultural and livestock products represents a strategic opportunity to enhance rural economic resilience and reduce greenhouse gas emissions in the food sector. This paper presents an original, policy-oriented framework that connects Km 0 distribution models with measurable CO2 reductions, proposing a structured system of economic incentives to support their adoption. Grounded in a mixed-methods approach, including normative analysis, empirical modeling, and a regional case study in Galicia, Spain, we demonstrate the alignment of Km 0 policies with the EU’s Common Agricultural Policy (CAP) 2023–2027 and the Sustainable Development Goals (SDGs). Findings reveal substantial potential for environmental mitigation, improved farm profitability, and revitalization of rural economies. This work provides a comprehensive roadmap for integrating Km 0 into national agricultural strategies, supported by data-driven justification and scalable implementation models.